2021
DOI: 10.21037/atm-20-4802
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of acute pancreatitis and its diagnosis, pathogenetic mechanism, and management

Abstract: Acute pancreatitis (AP) is an inflammatory disease that can progress to severe acute pancreatitis (SAP), which increases the risk of death. AP is characterized by inappropriate activation of trypsinogen, infiltration of inflammatory cells, and destruction of secretory cells. Other contributing factors may include calcium (Ca 2+ ) overload, mitochondrial dysfunction, impaired autophagy, and endoplasmic reticulum (ER) stress. In addition, exosomes are also associated with pathophysiological processes of many hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 179 publications
(209 reference statements)
0
40
0
12
Order By: Relevance
“…In the past, treatment of FCS patients was limited to very strict dietary fat restriction and avoidance of alcohol and certain medications. [ 3 , 11 ] Plasmapheresis has been tried in some FCS cases. [ 12 ] In the presence of diabetes, intravenous administration of insulin is required.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, treatment of FCS patients was limited to very strict dietary fat restriction and avoidance of alcohol and certain medications. [ 3 , 11 ] Plasmapheresis has been tried in some FCS cases. [ 12 ] In the presence of diabetes, intravenous administration of insulin is required.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the accessibility and usability of CT creates a trend for physicians to refer to this examination more frequently for research purposes. An advanced CT scan is the most effective method for diagnosing acute pancreatitis and pancreatic necrosis, with typical features on cross-sectional imaging such as pancreatic enlargement, pancreatic edema, uneven density, peripancreatic fat shift, and fluid collection 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have reported that although abdominal CT can identify pancreatitis in the early phase of the disease course, it will not contribute to the diagnostic sensitivity and may be negative if performed too early [13][14][15] . However, it is accepted that CT imaging can be used if the possibility of necrotizing pancreatitis is suspected in severe cases 8,11,16,17 . As a result of all these, the use of CT remains limited unless there are other conditions that should be evaluated in the differential diagnosis of acute pancreatitis cases in emergency services 8 In the study conducted by Yardan et al 9 , 52 (85.2%) of the patients with acute pancreatitis in the emergency department underwent abdominal CT, and 32 (61.5%) of the patients who were performed abdominal CT had mild clinical manifestations, 20 (38.5%) had severe.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular events important to the pathogenesis of AP include pathological calcium signaling (10)(11)(12), premature trypsinogen activation within macrophages and acinar cells (13)(14)(15), mitochondrial dysfunction (16,17), endoplasmic reticulum (ER) stress (18,19), impaired autophagy, and impaired unfolded protein response (UPR) (17). These events are caused by usual acinar cell toxins, such as nicotine, alcohol, and bile acids.…”
Section: Incidencementioning
confidence: 99%